SPORT TRAINING CHARACTERISTICS OF YOUNG CYCLISTS - Iv. Kolev (Trakia Journal of Sciences)
The purpose of this theoretical study is to reveal the peculiarities of preparation in young cyclists. The study was conducted using the methods: study of literary sources and documentary materials, theoretical analysis and synthesis. Analysis of results. Sports cycling training is a multi-year process requiring long and hard work with young cyclists, who are a reserve of high sportsmanship. Conclusions.Based on the theoretical analysis, we can draw the following generalized conclusions: From the proper planning and implementation of the training loads depends on reaching a good sports form from children, adolescents and girls to men and women preparing to participate in international competitions and to reach the level of sports mastery.